Use of protected fat sources to reduce fatty acid biohydrogenation and improve abomasal flow in dry dairy cows - Bettero, Vitor Pereira [UNESP]; Del Valle, Tiago Antônio; Barletta, Rafael Villela; de Araújo, Cybele Emília; Ferreira de Jesus, Elmeson [UNESP]; de Almeida, Gustavo Ferreira; Takiya, Caio Seiti; Zanferari, Filipe; de Paiva, Pablo Gomes [UNESP]; de Freitas Júnior, José Esler; Rennó, Francisco Palma (Elsevier, 2017)
The objective of this study was to evaluate the effects of dietary fat supplementation on dry dairy cows feed intake, digestion, ruminal kinetics, biohydrogenation, and abomasal flow of fatty acids (FAs). Eight Holstein rumen and abomasum fistulated dry cows (average body weight of 614 ± 59 kg), were assigned to a replicated 4 × 4 Latin square design experiment, with 21-d periods. The experimental diets were: 1) control (CON): corn- and soybean meal-based diet, with no fat source; 2) soybean oil (SO) diet with 30 g/kg dry matter (DM) of soybean oil; 3) whole raw soybean (WS) diet with 160 g/kg DM of whole raw soybean grain; 4) calcium salts of fatty acids (CS) diet with 32 g/kg DM of calcium salts of unsaturated FA. Fat-supplemented diets increased ether extract intake and digestibility without affecting DM intake. However, these diets promoted a decrease in DM and neutral-detergent fiber (NDF) total tract apparent digestibility. Fat sources decreased ruminal acetate to propionate ratio (C2:C3). In addition, SO diet increased ruminal propionate concentration and decreased C2:C3 in relation to protected sources of FA (CS and WS). Furthermore, cows fed CS diet exhibited higher ruminal pH, NH3-N and acetate concentration compared to those fed WS diet. Fatty acid supplementation did not alter serum glucose and urea concentration, but increased the serum cholesterol concentration. Although FA supplementation increased net energy intake of cows, energy and nitrogen balances, and microbial protein synthesis were not affected by the experimental diets. Fat supplementation had no effect on ruminal digestion neither on DM and NDF passage rates. Cows fed CS and WS diets presented higher DM and NDF ruminal digestion rates whether compared to SO one. Consequently, cows fed CS and WS had higher truly digestible NDF ruminal removal rate than those fed SO. Calcium salts of unsaturated FA increased DM and NDF rumen passage rate and decreased NDF digestibility in relation to WS diet. Fat-supplemented diets increased the abomasal flows of C18:2, trans C18:1, C18:0, C16:0 and total FA. The CS supplementation resulted in a higher abomasal flow of DM, total FA, trans C18:1, C16:0 and C18:3 when compared to WS one. On the one hand, FA supplementation increased C18:2 and C18:1 biohydrogenation rates; on the other hand, it protected FA sources decreased C18:2 and C18:1 biohydrogenation rates. In conclusion, fat-protected sources were effective to prevent FA from ruminal biohydrogenation.
Keywords: High-forage diets; Linoleic acid; Lipids; Passage rate; Ruminal digestibility